Organizational Development and Change Managementof EEI Power Corporation - Antonette Belago; Allan Calderon; Leonardo Thenov; Elizabeth Furio Perez (Journal of Strategic Innovation and Business Management, 2025)
Organizational Development and Change Management (ODCM) is vital for companies to succeed and grow. The study focused on the Organizational Development and Change Management of EEI Power Corporation. The descriptive method was used with the financial statement to determine if the 7s framework were significant to firm’s efficiency. The finding showed that Shared Values, Skills, Style, Staff, Strategy, Structure and Systems were Effective. The Study recommends to look into the improvement of 7s framework specifically to improve Shared Service, Strategy, and Skills of EEI Power Corporation. The research contributes empirical evidence on the impact of 7s Framework to Organization Development and Change Management of EEI Power Corporation.